Kesiapan Belajar Peserta Didik terhadap Pemahaman Sains di Era Revolusi Industri 4.0 - Gusmaweti Gusmaweti; Ovi Zurah Mei (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2021)
This study aims to analyze students' learning readiness to understand science in the Industrial Revolution 4.0 Era. The type of research used is descriptive research with the number of samples selected based on proportional random sampling as many as 123 people. The results showed that the level of readiness of students in the Collaboration aspect skills was 3.63, Critical Thinking and Problem Solving was 3.36, Creativity and Innovation was 3.35 and Communication was 3.33. The level of student learning readiness has a positive effect on science understanding (learning outcomes) of science, with the relative contribution of students' learning readiness to science understanding is 54.7%. In conclusion, the level of students' learning readiness for understanding science in the face of the Industrial Revolution 4.0 is included in the ready category. Keywords: Learning, Industrial Revolution 4.0 Era, Readiness, Science Understanding